Принцесса и Ангел: роман / Д. Стоун - Стоун Диана (Панорама романов о любви, 2008)
Экземпляры: ф.1 (20180117) / Инвентарный номер: 41931 / Цена: 20.00 / Авт.знак: С 81 / ГРНТИ: 17.82 / ББК: 84(7Сое)-44